Wpływ koncepcji małżeństwa na rozumienie zdolności konsensualnej w okresie poprzedzającym promulgację KPK z 1983 r. - Góralski, Wojciech (Ius Matrimoniale, 2015)
The question about the consensual ability, especially its minimum, has been visible in the doctrine of canonical marital law in the period preceding the CIC from 1983. To specify who is able to enter into marriage, the fundamental criterion is the proper understanding of the very marital reality. Regarding the vision of consensual ability, related strictly to the perception of marriage and its very nature, in the considered period special attention needs to be paid to the doctrine of a prominent modern Spanish canonist and philosopher J. Hervada. Its legitimacy can be vividly seen against the background of other theories, whose main representatives, although presenting different opinions (although having a lot in common) are, inter alia, P. Gasparri and J. R. Keating. Gasparri’s concept of marriage is a contract (matrimonium in fieri), which is the fountain of the relationship of mutual justice between spouses. Keating, however, strives to integrate the perception of marriage in fieri with the marriage in facto esse. The marital ability would not only be the ability to the act of marital congruence, but also the ability to live in marriage. According to Hervada, the essence of marriage in facto esse is the legal bond being “unity in natures” prior to any action of the married couple as such. The mentioned canonist attaches significant importance to the capacitas underlining that it should be referred to the act of entering into marriage, it is about the ability to undertake this act not about the ability ad statum coniugalem. He opines that the causes of incapacitas treated in reference to this unity of spouses may cause the invalidity of marriage only if they stand in the way of “unity in natures”.